RELIGIOUS COURT COMPETENCE IN SHARIA ECONOMIC DISPUTE COMPLETION - Dhaifina Fitriani (Muamalat: Jurnal Kajian Hukum Ekonomi Syariah, 2020)
Sharia economic problems are problems that are still new and not well known in the legal world. The competence of the Religious Courts in sharia economic matters is mentioned in Law Number 21 of 2008 concerning Sharia Banking which provides competence to the Religious Courts in handling sharia economic matters (disputes). The authority of the Religious Courts in Law No. 3/2006 confirms that "the Religious Courts are one of the perpetrators of judicial authority for the people who seek justice in the Muslim religion regarding certain cases." Religious Courts should have practically had competence in handling sharia economic matters. However, in reality, the justification of the competence of the Religious Courts in resolving sharia economic matters is still being debated. This paper uses analysis studies (analysis studies) by collecting primary data and secondary data from library research (library research) and using a juridical normative approach in analyzing data.